Proceedings of the 9th Annual Conference on Genetic and Evolutionary Computation 2007
DOI: 10.1145/1276958.1277197
|View full text |Cite
|
Sign up to set email alerts
|

Genetic multi-step search in interpolation and extrapolation domain

Abstract: The deterministic Multi-step Crossover Fusion (dMSXF) is an improved crossover method of MSXF which is a promising method of JSP, and it shows high availability in TSP. Both of these crossover methods introduce a neighborhood structure and distance in each permutation problem and perform multi-step searches in the interpolation domain focusing on inheritance of parents' characteristic. They cannot work effectively when parents stand close each other since they search in interpolation domain. Therefore in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…dMSMF has been shown to outperform other heuristic methods under the definition of sophisticated neighborhood structures and distance metrics on JSP and traveling salesman problem (TSP) [11].…”
Section: B Deterministic Multi-step Crossover Fusionmentioning
confidence: 99%
See 2 more Smart Citations
“…dMSMF has been shown to outperform other heuristic methods under the definition of sophisticated neighborhood structures and distance metrics on JSP and traveling salesman problem (TSP) [11].…”
Section: B Deterministic Multi-step Crossover Fusionmentioning
confidence: 99%
“…This model focuses on a local search performance and it showed effectiveness in combinatorial optimization problems [3], [10], [11]. , xi+1), select the best individual c from offspring C(xi, xi+1) generated by parents (xi, xi+1) and replace the parent xi with c. 6.…”
Section: Generation Alternation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The acquisition of characteristics that do not appear in the parents can be achieved by incorporating deterministic Multi-step Mutation Fusion (dMSMF) 20) into dMSXF. dMSMF also performs a multistep neighborhood search and explores the external domain of the population distribution.…”
Section: Genetic Multistep Searchesmentioning
confidence: 99%
“…Deterministic Multi-step Mutation Fusion (dMSMF) is a complementary search method to dMSXF and explores outside the distribution of the population. It has been shown that the incorporation of dMSMF into dMSXF improves the search performance in several combinatorial problems 20) . In addition, we have shown that the high search performance of both dMSXF and dMSMF was achieved by setting the neighborhood size to a value near the correlation length, which is an indicator of the level of epistasis 21) .…”
Section: Introductionmentioning
confidence: 99%